2009
DOI: 10.1037/a0013253
|View full text |Cite
|
Sign up to set email alerts
|

A college suicide prevention model for American Indian students.

Abstract: College student suicide prevention efforts are important to campus administrators and mental health professionals due to increasing concerns about managing suicidal students. This article describes the development and preliminary effectiveness of a campus suicide prevention program designed for American Indian (AI) students who are at higher risk for suicide compared with the general population. Using the medicine wheel as a guiding framework, the current prevention model integrates communication links between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 21 publications
(23 reference statements)
1
49
0
1
Order By: Relevance
“…Five intervention evaluations targeted Native Americans [37,39-42]; three targeted Aboriginal Australians [35,36,38,43] and one First Nation Canadians (Inuit) [34]. No interventions targeted the Maori of New Zealand.…”
Section: Resultsmentioning
confidence: 99%
“…Five intervention evaluations targeted Native Americans [37,39-42]; three targeted Aboriginal Australians [35,36,38,43] and one First Nation Canadians (Inuit) [34]. No interventions targeted the Maori of New Zealand.…”
Section: Resultsmentioning
confidence: 99%
“…Muehlenkamp et al (2009) demonstrated this in a regional public institution in the upper Midwest. They showed that many American Indian students lacked the skills and knowledge to deal with suicide as part of the college experience.…”
Section: Literature On Program Effectivenessmentioning
confidence: 90%
“…The barriers include: inability to participate in cultural celebrations and traditions due to lack of proximity to their native reservation, lack of culturally sensitive staff in the universities' health system, and lack of culturally appropriate education techniques exhibited in these sensitive matters. Moreover, Muehlenkamp et al (2009) noted that students' emotional distress is often not noted as a serious event affecting the relative reservation of the students, which often goes unknown to the non-American Indian health practitioners on campus. This underscores the need for student helpers, much like natural helpers of the reservation, to be used to distribute information to the university staff.…”
Section: Literature On Program Effectivenessmentioning
confidence: 97%
See 1 more Smart Citation
“…Final year students more often considered suicide to be an expression of psychiatric disease and thought that people trying to commit suicide were not responsible for their own actions. Muehlenkamp et al (2009) presented a model for college suicide prevention American Indian students who were at higher risk for suicide compared with the general population. They offered a discussion of the barriers faced and solutions generated for implementing the program along with recommendations for disseminating this AI-specific prevention program to other universities.…”
Section: Introductionmentioning
confidence: 99%